An Analysis of Illocutionary Speech Acts in the Book - Rochmat Budi Santoso (Kawalu: Journal of Local Culture, 2017)
This study aims at finding out how the Searle’s illocutionary speech acts are most frequently used and performed in the book “Paparaton: Leg-enda Ken Arok dan Ken Dedes”. The researcher uses qualitative meth-od by collecting data from reading the book, analyzing the dialogues of each characters, reading the script and doing library research. The total of the classification illocutionary speech acts according to Searle are 39 speech acts. The result of analysis shows that there are 9 commisives of illocutionary speech acts (23%). There are 9 representatives of illocution-ary speech acts (23%). There are 7 expressive of illocutionary speech acts (18%). There are 14 directives of illocutionary speech acts (38%). It is not found declaration of illocutionary acts in this book. The study also reveals the importance of illocutionary speech acts in keeping the flow of storyline of the book. This study expected to give some useful insights in understanding what illocutionary speech acts.Keywords: Speech acts, Paparaton “Legenda Ken Dedes dan Ken Arok”, Dia-logue